1 - Editorial Note - Journal System, (Africa Development, 1984)
In late 1983, Africa Development began receiving what could only be described as a flood of articles from Nigeria. While these articles covered all aspects of socio-economic development in Nigeria (transporation, presidential politics, corruption, industrialization etc...), a dominant theme soon emerged: namely, the deepening economic and Social crisis in Nigeria. After some deliberation, the editorial committee of Africa Development decided that the best way to handle this flood was to put together a Special Issue on the crisis in Nigeria and, to that end, invited Professor Claude AKE of the University of Port Harcourt to be the Guest Editor for this number. Much to our surprise, Africa Development received in December 1983, a copy of the Green Paper on the State of the Nigerian Economy for possible publication. The reaction of the editorial committee was enthu- siastic, to say the least, for a number of reasons. 1 - The Green Paper is the product of a workshop organized by our Colleagues at Ahmadu Bello Uni- versity on the State of the Nigerian economy and it represented the views of a wide cross-section of the Nigerian public: scholars, government offi- cials, trade-unionists, businessmen and politicians. 2 - The Green Paper addressed itself to the Federal Government White Paper on the recommen- dations of the National Economic Council, itself based on the recommenda- tions of the Committee of Experts under the Chairmanship of Dr. J.S. OD AM A (The OD AM A Report). The events of December 31st 1983, however, dampened the en- thusiasm of the Editorial Committee somewhat: the hasty conclusion reached was that the ODAMA Report was a dead letter thus the raison d'être for the publication of the Green Paper no longer existed. More fundamentally, December 3 1st raised serious questions to social scientists all over Africa as to the social and political significance of the return to military rule. We note that in his introduction to this special issue, the Guest Editor attempted to analyze precisely these issues. The Revised Budget Speech of May 1984 outlined the Federal Military Governments perceptions of the nature of the crisis and set forth a first set of solutions to them. In the view of the Editorial Committee therefore, the publication of the 1984 Budget Speech in its entirety became a must. The Federal Military Government has been in power for about a year now, during which time a number of economic policies have been undertaken to cope with the deepening economic crisis. In view of these policies and the on-going debate in Nigeria and outside, on the nature of the crisis, the Editorial Committee now feels that the Green Paper and the ODAMA Report are of continuing relevance: Thus the decision to publish both. Technical problems delayed the publication of this Special Issue but the delay worked to the advantage of Africa Development because it permitted the publication of the January 1985 Budget Speech of the Federal Military Government, which mapped not just the policies for 1985 but contained an assessment of the performance of the Nigerian econonn tor the year 1984 as well.